Comparison of stroke warning sign campaigns in Australia, England, and Canada. (27th September 2012) - Trobbiani, Kym; Freeman, Kate; Arango, Manuel; Lalor, Erin; Jenkinson, Damian; Thrift, Amanda G.
Abstract : Background: Public awareness of the signs of stroke is essential to ensure that those affected by stroke arrive at the hospital in time for lifesaving therapies. It is unclear how well stroke awareness campaigns improve awareness of stroke signs and whether people translate this into action. Methods: We evaluated stroke awareness campaigns conducted in England, Australia, and Canada using pre‐ and post‐campaign surveys. We assessed the proportion of people who could name the main signs of stroke, and compared the proportion naming these correctly between locations. We also assessed whether people would call emergency services in the event of a stroke. Proportion responding correctly was compared using chi‐square analysis. Results: The amount spent on the campaigns was different in each country. The post‐campaign survey was conducted among 400 people in Australia, 1921 in England, and 2703 in Canada. Sixty‐eight per cent of people in Australia and 57% in Canada could name two or more signs of stroke ( P  < 0·001). After the campaign, knowledge of each of the elements of the campaign (face, arm, speech, time) was significantly greater in England than in Australia ( P  < 0·001 for each item). A high proportion of participants reported that they would call emergency services in the event of a stroke (97% in England, 90% in Australia, and 67% in Canada). Conclusion: Knowledge of stroke signs and the action to be taken can be improved with awareness campaigns. The effectiveness of these campaigns may be enhanced by spend on media, media mix, and key messages. It is critical to ensure that campaigns provide the clear and bold message that prompt action is an essential ingredient to reduce death and disability following stroke.